The Japanese low Fodmap diet manual - Uno, Yoshiharu (CAMBRIDGE SCHOLARS PUBLISHING, 2019)
Before World War II, Japanese people ate an abundance of rice and fish. Now, however, many of them are eating wheat instead of rice. Most Japanese are lactose intolerant, but they consume milk and yoghurt every day. Furthermore, fructose in fruits has been increased by breeding improvement, and oligosaccharides and sorbitol have been added to processed food made in Japan. Do these high-FODMAPs cause disease? Specifically, have they contributed to the rapid rise of irritable bowel syndrome (IBS) and inflammatory bowel disease in Japan?This book is the English version of a Japanese publication f.